Modelling and simulation of natural fibre/epoxy composites - prediction of stress state and deformations. (15th May 2019) - Prabhakaran, R.T. Durai; Gupta, Mohit; Mahajan, Puneet; Ormondroyd, Graham A.
Natural fibres usually include hemp, jute, and flax fibres are gaining importance in composites with an increasing potential to replace synthetic fibres in advanced composites. Current glass and carbon fibre systems require large amount of energy in production, which has led to an upsurge in interest in the reinforcement potential of natural fibres. Especially with natural fibres, higher variability of mechanical properties is a major challenge. Therefore, prediction of laminate performance at early stages of design requires computation. The present work was intended to understand how the flax fibre layups and orientation affect the mechanical behaviour of laminated composites. Unidirectional, cross-ply, angle-ply, and quasi-isotropic laminates made up of flax fibre reinforced epoxy are considered to study tensile, flexural behaviour, and stress distribution in the individual laminae. A classical laminate theory, which considers elastic behaviour of the laminae, and a finite element simulation are used to predict the stress-strain response of a layered composite. Further, results showed that the quasi-isotropic flax/epoxy laminate perform better than angle-ply and cross ply laminates.